PENGARUH HARGA DAN KUALITAS PAKAIAN BEKAS TERHADAP KEPUTUSAN PEMBELIAN (STUDI KASUS PADA THRIFTING KOTA SERANG) - Alifi Hidayat; Aisyah Putri Fadillah; Akmaluddin Akmaluddin; Wahyu Hidayat (Jurnal Kendali Akuntansi, 2023)
This study examines the effect of the price and quality of used clothing on the purchasing decisions of used clothing among residents of Serang City. The study population consisted of 40 people, all genders, who bought Used Clothing products. Data were obtained by distributing questionnaires to 40 respondents from Serang City residents. Based on research, the buyer's decision on used clothing (Serang City Thrifting) has a positive and quite large impact on price and quality.